Hygienic Processing Technique For Quality Pig Casing Manufacture - Thankachan OT (Department of Livestock Products Technology, College of Veterinary and Animal Sciences, 1997)
The fresh small intestines of Large White Yorkshire pigs slaughtered in the Meat Technology Unit were harvested in order to evolve a suitable technique for the hygienic production and storage of pig rounds and to study the economic feasibility of its production. All the pigs were 8-9 months old and of the body weight 70-90 kg and maintained on the same nutritional status. The efficiency of sliming of the pig small intestine by the fermentation technique and by different concentrations of alkaline chemicals such as calcium hydroxide, sodium carbonate, sodium bicarbonate and sodium hydroxide was studied. The various quality parameters of the pig rounds such as cleanliness, appearance, yield, calibre, strength, texture, aerobic mesophilic counts on storage, shelf life and organoleptic qualities after stuffing with fresh pork sausage mix were evaluated. The economic feasibility of production of the rounds was also computed. The pig rounds processed were clean, white, almost transparent and without holes or cuts. The mean length of the round was 17.9 m and the yield was 77.6%. The rounds obtained were of 'Narrow' grade having 29 mm diameter. The casings were strong enough to withstand the pressure of stuffing.